Consuming Mung Beans (Phaseolus radiatus L.) Increase Hemoglobin Levels among Pregnant Women with Anemia in The Second Trimester at Klenang Public Health Centre, Probolinggo District - Hidayati, Tutik; Holila, Roviatun (Journal of Health Sciences, 2021)
Anemia in pregnancy is a pregnant mother with hemoglobin levels below 11 g/dL in the first and third trimesters or hemoglobin levels less than 10.5 g/dL in the second trimester. This paper investigates the effect of consuming mung beans (Phaseolus radiatus L.) on hemoglobin levels in the Second trimester of pregnant women with anemia. This research used a quasi-experimental design with randomized pretest-Posttest with a control group design. The population was 37 pregnant women in the second trimester who experienced anemia at Klenang PHC. Meanwhile, the sample was 34 respondents by simple random sampling. The independent variable was consuming mung beans, while the dependent variable was the hemoglobin levels. In the control group, the authors observed the consumption of Fe tablets once a day for 20 days in 17 respondents. While in the intervention group, we monitored the consumption of Fe tablets once a day and were given mung bean juice every day for 20 days in 17 respondents. The instrument used an observation sheet and a digital hemoglobin measuring device. Then, data analysis utilized the paired sample t-test with a significance of 0.05. After consuming mung beans and Fe supplements, the average hemoglobin levels in the intervention group were 12.1588g/dL. Meanwhile, in the intervention group, after Fe observation were 10.6412d/dL. There was a significant difference between the control and intervention groups p=0.000 (p<0.05). In conclusion, consuming mung beans increases hemoglobin levels among pregnant women with anemia in the second trimester.